2019
DOI: 10.1097/01.ju.0000554867.66478.23
|View full text |Cite
|
Sign up to set email alerts
|

Mp01-03 rezūm Water Vapour Ablation Therapy for Benign Prostatic Hyperplasia: Initial Results From the United Kingdom

Abstract: Surgical options are limited when treating large (>80cc) prostates for lower urinary tract symptoms (LUTS) due to benign prostatic hyperplasia (BPH); there is a need for novel surgical approaches with shorter learning curves and effective treatment. Aquablation (AquaBeam System, PROCEPT Bio-Robotics, Inc., USA), an ultrasound-guided, robotically executed waterjet ablative procedure, could be this novel tool. This analysis compares the outcomes of Aquablation in 30cc to 80cc prostates with the outcomes in 80cc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Additionally, randomized control trials have shown a reduction in symptomatic LUTS (storage and voiding symptoms) at four years with a mean IPSS improvement of 47% with Rezum therapy [10]. Lastly, due to the COVID-19 pandemic, and the favorability of reducing operative times, Rezum proves as a suitable option with each procedure reported to average around [17.5 minutes] when compared to 60-90 minutes with TURP [16].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, randomized control trials have shown a reduction in symptomatic LUTS (storage and voiding symptoms) at four years with a mean IPSS improvement of 47% with Rezum therapy [10]. Lastly, due to the COVID-19 pandemic, and the favorability of reducing operative times, Rezum proves as a suitable option with each procedure reported to average around [17.5 minutes] when compared to 60-90 minutes with TURP [16].…”
Section: Discussionmentioning
confidence: 99%
“…Randomized control trials have also shown a reduction in symptomatic LUTS at four years with an average IPSS improvement with Rezum therapy of 47% (10). Lastly, due to COVID-19 and the benefit of reducing operative time, Rezum has proven to be a good choice with each procedure being reported to take about 17.5 minutes compared with 60-90 minutes for TURP (16). The efficacy of Rezum in the Arab population has not been extensively studied since the introduction of this novel therapy.…”
Section: Discussionmentioning
confidence: 99%